Plotinus on Love: An Introduction to His Metaphysics through the Concept of Eros - Bertozzi, Alberto, (Philosophia Antiqua ;, 2020)
Plotinus' metaphysics is often portrayed as comprising two movements: the derivation of all reality from a single source, the One, and the return of the individual soul to it. Alberto Bertozzi argues that love is the origin, culmination, and regulative force of this double movement. The One is both the self-loving source of the derivation and articulation of all reality in levels of unity and love and the ultimate goal of the longing of the soul, whose return to its source is a gradual transformation of the love it originally received from the One. Touching on virtually all major concepts of Plotinus' philosophy, Plotinus on Love is at once an investigation of a lesser-studied Plotinian theme and an introduction to his metaphysics.